ANALYSIS OF THE NEEDS FOR DEVELOPING E-MODULES WITH FLIPPING BOOKS AS ETHNOMATHEMATICS-BASED TEACHING MATERIALS - Pirma, Fitri Oktaria; Caswita, Caswita (Universitas Sembilanbelas November Kolaka, 2023)
This research is research on the development of teaching materials in the form of e-modules based on ethnomathematics. This type is a qualitative descriptive research. The research data collection instruments were form of teacher needs analysis interview sheets, and student needs analysis questionnaires. The teaching material developed is the form of an e-module using a Flipping book. The research subjects consisted of a teacher and 28 grade VIII junior high school students. The results of the needs analysis obtained that 78.6% of students answered that they had textbooks or other guidelines but 61% of students answered that they did not look for learning materials anymore only from school books, as many as 75% of students wanted to learn using teaching materials other than textbooks or worksheets, then as much as 82% answered that the learning media used by teachers didn’t contain culture in mathematical concepts, and 71% of students thought that it was necessary to use media e- modules based on ethnomathematics to learn mathematical concepts in culture. These results indicate that it needed to develop teaching materials e-modules based on ethnomathematics.